Syntheses and Antimicrobial Activities of the Naphthalenyl-ethenylpyridinium Benzenesulfonate Derivatives - Kullapa Chanawanno (Prince of Songkla University, 2016)
Thesis (M.Sc.,Inorganic Chemistry)--Prince of Songkla University, 2010